2012
DOI: 10.1590/s0102-86502012000900001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative immunohistochemical analysis of duodenal ghrelin cells after sleeve gastrectomy in Wistar rats

Abstract: PURPOSE: Sleeve gastrectomy (SG) removes substantial part of the gastric mucosa, which produces ghrelin. This reduction is expected to force other organs, such as the duodenum, to compensate by increasing the number of ghrelin-producing cells. The purpose of this study was to evaluate whether this response occurs. METHODS: Twelve adult male, Wistar rats underwent SG and were reoperated 30 or 60 days after the initial surgery. During the second surgery, a segment of the duodenum was resected to count ghrelin ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…These results may depend on a different hormonal response induced by resection. 29,30 In fact, in these cases, we observed a rapid control of glucose levels: at 6 months of follow up we observed similar results to those obtained at 12 postoperative months for resection inferior to 1800 mL. In our opinion, the rapid stabilization of glucose levels and blood pressure indicate a major hormonal depletion induced by a major gastric resection.…”
Section: Sista F Et Al Int Surg J 2016 Feb;3(1):11-17supporting
confidence: 83%
See 1 more Smart Citation
“…These results may depend on a different hormonal response induced by resection. 29,30 In fact, in these cases, we observed a rapid control of glucose levels: at 6 months of follow up we observed similar results to those obtained at 12 postoperative months for resection inferior to 1800 mL. In our opinion, the rapid stabilization of glucose levels and blood pressure indicate a major hormonal depletion induced by a major gastric resection.…”
Section: Sista F Et Al Int Surg J 2016 Feb;3(1):11-17supporting
confidence: 83%
“…Some animal studies show an overexpression of ghrelin secreting duodenal cells several months after gastric resection, and a subsequent increase in hormonal blood levels. 30 Once confirmed in humans, these data could justify the different metabolic reaction in patients with an RGV>1800 mL. Further studies on hormonal signaling, especially ghrelin, are actually in progress in our Department to support this hypothesis.…”
Section: Sista F Et Al Int Surg J 2016 Feb;3(1):11-17supporting
confidence: 54%
“…In the long term, postoperative plasma ghrelin levels sometimes approach preoperative levels in patients who have undergone distal gastrectomy. It has been reported that the number of ghrelin-producing cells does not increase after gastrectomy [39]. Persistent low body weight after gastrectomy might stimulate ghrelin secretion from individual ghrelin-producing cells in a negative feedback manner.…”
Section: Gastrectomy and Ghrelin Secretionmentioning
confidence: 94%
“…Unfortunately, literature concerning the consequences of gastrectomy on the expression of the hormones assessed in the present study is very limited. Teive et al [78] observed no significant changes in the number of ghrelin-positive cells in the duodenum of rats after SG.…”
Section: Discussionmentioning
confidence: 95%